Pelecehan Seksual di Kalangan Pelajar Menurut Fiqh Jinayah dan UU No. 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual Studi Kasus Kecamatan Wampu Kabupaten Langkat - Astuti, Puji Tri; Marpaung, Aripin; Lubis, Syofiati (MASALIQ, 2023)
Criminal acts do not yet have provisions that are expressly contained in Islamic law. Al-Quran and hadith do not explicitly regulate this issue. That is, regarding legal matters of understanding sexuality it is not mentioned in the realm of ḥudud's finger, the same is the case with adultery. The handling of juridical cases that limit sexual orientation experiences problems, especially regarding the formulation of criminal acts or delicts. The type of research used is through comparative sociological normative methods. Normative research is carried out by examining library materials which are secondary data, while sociological/empirical legal research methods are carried out by examining primary data obtained directly in the community. This study also uses a comparative approach (Comparative Approach) is research that is comparative in nature, which is compared both in the form of similarities and differences. The results showed that: 1) Sexual harassment is an act that includes dirty or indecent verbal expressions (comments, jokes and so on), indecent behavior, showing pornographic/obscene images, assault and indecent coercion such as forcing to kiss and hugging, threatening to buy a woman if she refuses to provide sexual services, to deception. Factors that influence the occurrence of sexual division among students are internal and external factors.